Analysis of Expressive Illocutionary Acts in Disney Princess Movie “Moana” - Mohamad Syafri; Nanik Shobikah; Zulfikar Zulfikar (Universitas Negeri Makassar, 2025)
Abstract. Movies are a reflection of real-life phenomena, including the language phenomenon. Therefore, using the movie from Disney “Moana”, this research analyzes expressive illocutionary acts. As part of the broader speech act theory, expressive acts convey the speaker's psychological state, such as apologizing, thanking, congratulating, wishing, greeting, and expressing attitudes. This study is a descriptive qualitative study through content analysis, using Moana’s movie script as the primary data source. Data were collected through viewing, note-taking, classification, and analysis. Dell Hymes’ SPEAKING model and lexical analysis via AntConc were the primary data analysis methods. The findings reveal that four types of illocutionary acts appear in the film—expressive, commissive, directive, and representative—while declarative acts are absent. Among 559 illocutionary utterances identified, 34% (190) were expressive.